An Example of a Model for the Protection of the Right to Education for Children Who Work - Mashendra (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
The right of children who are employed to receive an education is called into question in this study. In order to develop an optimal model for protecting the right to education for working children, the purpose of this research is to identify the regulations that govern working children in Indonesian laws and regulations. A normative legal research approach is utilized in this study. A study of laws was carried out by researchers in order to compare and contrast the various pieces of legislation. In the process of analyzing the findings of research, both human rights theory and statutory theory are utilized as analytical tools. The findings of this study lead to the conclusion that, first and foremost, the government has protected the rights of children in accordance with a number of laws and other rules. Regarding the rights of minors who are employed, there are regulations that are quite clear. Second, the utilization of a circle of protection is the most appropriate and perfect model for safeguarding the educational rights of children who are employed. Protecting children who are employed in order to ensure that they are able to exercise their right to receive an education is the purpose of the circle of protection. There are various parties within the circle of protection that are responsible for protecting children who are employed. These parties include the government, parents, employers, and the community.